Akuntan Yang Unggul, Kinerja Keuangan Yang Unggul: Peran Mediasi Berurutan Antara Ketersediaan Ti Dan Kualitas Laporan Keuangan - Ujang Syaiful Hidayat; Rudiana Fibriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The rapid development of technology has resulted in many corporate entities adopting digital AIS, while accountants are still trying to catch up with their competencies in the use of IT. This study was conducted to examine the effect of accountant competence on IT availability, financial report quality and financial performance, with the novelty of testing sequential mediation of IT availability and financial report quality. The researcher distributed questionnaires to 110 staff accountants in companies that adopted digital AIS, then the data were processed using SEM-PLS technique. This study found that although accountants have sufficient knowledge and skills, they still feel unfamiliar in using digital accounting information systems. On the other hand, the use of digital AIS can improve the quality of financial statements, but can reduce financial performance due to differences in SAK interpretation in digital AIS programming. However, the point is, quality financial reports, whether made manually or with digital AIS, can help users make the right decisions.